METHODICAL ASPECTS OF REALIZATION OF A LESSON WITH THE HELP OF THE PEDAGOGICAL SOFTWARE "ALGEBRA, 8 CLASSES". - L. Shishko; I. Chernenko (Kherson State University, 2009)
In this article is described the purpose of the pedagogical software "Algebra, 8 classes", its basic descriptions and methodical aspects of realization of a lesson in network variant.